Behavioral thermoregulation in older adults with cardiovascular co-morbidities. Issue 1 (2nd January 2018) - Schlader, Zachary J.; Coleman, Gregory L.; Sackett, James R.; Sarker, Suman; Chapman, Christopher L.; Hostler, David; Johnson, Blair D.
ABSTRACT: We tested the hypotheses that older adults with cardiovascular co-morbidities will demonstrate greater changes in body temperature and exaggerated changes in blood pressure before initiating thermal behavior. We studied twelve healthy younger adults (Younger, 25 ± 4 y) and six older adults ('At Risk', 67 ± 4 y) taking prescription medications for at least two of the following conditions: hypertension, type II diabetes, hypercholesterolemia. Subjects underwent a 90-min test in which they voluntarily moved between cool (18.1 ± 1.8°C, RH: 29 ± 5%) and warm (40.2 ± 0.3°C, RH: 20 ± 0%) rooms when they felt 'too cool' (C→W) or 'too warm' (W→C). Mean skin and intestinal temperatures and blood pressure were measured. Data were analyzed as a change from pretest baseline. Changes in mean skin temperature were not different between groups at C→W (Younger: +0.2 ± 0.8°C, 'At Risk': +0.7 ± 1.8°C, P = 0.51) or W→C (Younger: +2.7 ± 0.6°C, 'At Risk': +2.9 ± 1.9°C, P = 0.53). Changes in intestinal temperature were not different at C→W (Younger: 0.0 ± 0.1°C, 'At Risk': +0.1 ± 0.2, P = 0.11), but differed at W→C (-0.1 ± 0.2°C vs. +0.1 ± 0.3°C, P = 0.02). Systolic pressure at C→W increased (Younger: +10 ± 9 mmHg, 'At Risk': +24 ± 17 mmHg) and at W→C decreased (Younger: −4 ± 13 mmHg, 'At Risk': -23 ± 19 mmHg) to a greater extent in 'At Risk' (P ≤ 0.05). Differences were also apparent for diastolic pressure at C→W (Younger: −2 ± 4 mmHg, 'At Risk': +17 ± 23 mmHg, P < 0.01), but not at W→C (Younger Y: +4 ± 13 mmHg, 'At Risk': −1 ± 6 mmHg, P = 0.29). Despite little evidence for differential control of thermal behavior, the initiation of behavior in 'at risk' older adults is preceded by exaggerated blood pressure responses.